The Relationship of Smoking Behavior Towards Decreased Appetite (Anorexia) in S1 Nursing Students Stikes Yahyha Bima - Ayatullah Ayatullah (LP2M STIT Palapa Nusantara, 2018)
Smoking behavior is a related issue public health because it can cause various diseases even can cause death for both smokers and people nearby (passive smokers). The purpose of this study was to determine the relationship of smoking behavior to decreased appetite (anorexia). This research is a type of Descriptive Analytical research with Cross Sectional method, the population in this study is the student of S1 undergraduate of Nursing STIKES Yahya Bima in 2017. Sampling using Total Sampling Technique, obtained 50 respondents. The data were collected by using Questionnaire. Data that has been collected and then processed and analyzed using computer program Microsoft Exeldan Statistic program (SPSS) version 16.0. Data analysis included univariate analysis by finding frequency distribution, bivariate analysis with Chi-Square test (p <0,05) to know relation between variable and person test to know correlation strength. The result of bivariate analysis showed the correlation between smoking behavior and decreased appetite (p = 0.125 <0,05). The conclusion in this research is there is no correlation between smoking behavior with decreasing appetite in student of S1 Nursing STIKES Yahya Bima. It is recommended for male students STIKES Yahya Bima to change smoking behavior because it will affect health especially on respiratory system, rubalah healthy lifestyle with exercise and achievement. For nursing profession is expected to always promote healthy lifestyle without cigarette smoke.